Development of a computer based spirometer - 390524 Ruhiana Idayu Abd Hamid (Skudai : Universiti Teknologi Malaysia, 2000)
Project Paper (Bachelor of Electrical Engineering (Electronic)) - Universiti Teknologi Malaysia, 2000